A Path to Formalization: Exploring the E-Waste Informal Sector's Integration Amid the Transition to Circular Economy - Pandya, Dhyeya (Université d'Ottawa | University of Ottawa, 2024)
The growing e-waste problem, fueled by high consumption of electronics and electrical equipment (EEE) and resource scarcity poses serious health, safety, and environmental risks. The circular economy (CE) is presented as a sustainable solution for these concerns, though some stakeholders may struggle with adapting to increased demands like supply chain transparency, materials traceability, and technological advancement. Operating predominantly in the Global South, informal workers manage significant amounts of e-waste, handing nearly 18 billion kg of e-waste in 2022. Current CE research often overlooks their impacts and fails to fully address the social implications of circularity. This gap prompts investigation in aligning CE principles with broader sustainability goals, especially regarding the role of the informal sector in the transition to CE. Formalization emerges as a potential strategy, involving regulation, collaboration, and capacity building to improve resource recovery, livelihoods, and mitigate associated risks while defining the role of the informal sector in circular e-waste management. A comprehensive literature review with seven semi-structured interviews were utilized to explore the formalization of the informal e-waste sector in the context of the global transition to circularity. The main findings reveal that formalization in e-waste management is a complex, multifaceted process requiring legal frameworks, regulatory enforcement, and integration strategies like capacity building and partnerships. The study underscores the importance of integrating informal workers into regulatory frameworks and CE policies to improve resource recovery, reduce environmental impacts, and enhance socio-economic outcomes. The study finds that including informal workers' perspectives may work to enhance effectiveness and adoption of formalization initiatives as part of a just transition to circularity in the EEE value chain and e-waste management.
Keywords: circular economy; formalization; e-waste